Unretirement and the (re)construction of age in post-industrial America - John, Nicole L. (Kansas State University, 2017)
In the 21st century, millions of older adults in the United States are coming out of retirement to work. In some cases, inadequate benefits and savings force them out of retirement, especially when they or their spouses experience costly health problems. In other cases, older workers “unretire” after losing loved ones, or as they experience social loss and disengagement. These older workers seek companionship through work. Although many older workers enjoy aspects of the jobs they attain in unretirement, their compensation is often insufficient, forcing some of them to perpetually delay re-retiring. Such unretirement reverses decades of movement toward greater and earlier retirement for older adults and significantly affects cultural meanings of old age. Focusing on six different worksites in Kansas, I examine how older workers and employers socially and culturally re-construct age. Evidence from ethnographic observation and thirty-three in-depth interviews with older workers and their employers suggest that employers view older workers’ agedness as an asset they can exploit to cut costs and boost profits. In sharp contrast, many older employees’ younger co-workers and clients treat them as if agedness diminishes their competence and relevance in the workplace. This is particularly true for women, who struggle more than their male colleagues to fend off the negative labels some younger co-workers and clients attempt to apply to them. Ultimately, I find that old age is a valued human resource for employers, making older employees “ideal workers,” but the cumulative effects of older workers’ interactions in the workplaces tend, on balance, to devalue older age. Notably, the forces that promoted positive constructions of older age tend to be rooted in exploitation. Employers who idealize older workers do so to squeeze as much unpaid labor power out of them as possible. When older workers resist exploitative work assignments, they often become subject to negative labeling, as opposed to other kinds of “problem worker” labeling that younger workers might face. By specifying the mechanisms that produce harmful versus helpful constructions of age at work in traditional retirement years, my study contributes to the growing body of research on the relatively new phenomenon of unretirement in the United States.
Keywords: Unretirement; Social construction; Age construction; Retirement; Older workers